Boldenone Undecylenate-Mediated Hepatorenal Impairment by Oxidative Damage and Dysregulation of Heat Shock Protein 90 and Androgen Receptors Expressions: Vitamin C Preventive Role - Behairy, Amany; Mohamed, Wafaa A. M.; Ebraheim, Lamiaa L. M.; Soliman, Mohamed Mohamed; Abd-Elhakim, Yasmina M.; El-Sharkawy, Nabela I.; Saber, Taghred M.; El Deib, Maha M. (Frontiers in Pharmacology, 2021)
Boldenone Undecylenate (BLD) is a synthetic derivative of testosterone and a widely used anabolic androgenic steroid. The health risk of BLD use as a pharmaceutical or dietary supplement is still underestimated and under-reported. Vitamin C (VC) has been recognized as an antioxidant with prominent hepatorenal protective effects. This study investigated the possible preventive activity of VC against BLD-induced hepatorenal damage. Forty adult male Wistar rats were classified into five groups: control, vehicle control, VC (orally given 120 mg/kg b.wt./day), BLD (intramuscularly injected 5 mg/kg b.wt./week), and BLD+VC-treated groups. The experiment continued for eight weeks. Serum levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) were measured. Serum contents of total protein (TP), albumin (ALB), globulin, total cholesterol (TC), triglycerides (TG), high-density lipoprotein-cholesterol (HDL-C), low-density lipoprotein-cholesterol (LDL-C), and very-low-density lipoprotein–cholesterol (VLDL-C) were also assayed. Urea, creatinine, and uric acid levels were determined together with sodium and potassium electrolytes measuring. Moreover, oxidative stress indicators including reduced glutathione (GSH), glutathione peroxidase (GPx), glutathione-S-transferase (GST), and glutathione reductase (GSR) as well as malondialdehyde (MDA) levels were measured in both hepatic and renal tissues. Corresponding histological examination of renal and hepatic tissues was conducted. Besides, immunohistochemical evaluations for androgen receptors protein (AR) and heat shock protein 90 (Hsp 90) expressions were performed. BLD caused significant rises in serum ALT, AST, TP, ALB, TC, TG, LDL-C, VLDL-C, urea, creatinine, uric acid, potassium, and MDA levels. Further, BLD-injected rats showed significant declines in the serum levels of HDL-C, sodium, GSH, GPx, GST, and GSR. Besides, distinct histopathological perturbations were detected in renal and hepatic tissues of BLD-injected rats. AR and Hsp 90 immunoexpression were increased in hepatic and renal tissues. In contrast, VC significantly reversed the BLD-induced hepatorenal damage in co-treated rats but not ameliorated AR protein overexpression. VC could be an efficient preventive supplement for mitigating BLD-induced hepatorenal damage, possibly via controlling oxidative stress events.